2012
DOI: 10.1177/1533317511435662
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dietary Supplements for Cognitive Health

Abstract: We studied use of vitamins, minerals, herbs, and other dietary supplements for cognitive health. We refer to these products as supplements. Data were from the 2007 National Health Interview Survey, which asked about complementary and alternative medicine (n = 22 783). Chi-square and multivariate logistic analyses were weighted for national representativeness, accounting for the survey design. Among supplement users, about 8.8% of those without cognitive problems used them for cognitive health; 15.7% of those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“… 31 In one study, Laditka et al found that most of adults used supplements to treat or cure their cognitive problems rather than to prevent them. 32 Hence, this study provides scientific evidence of beneficial effect of natural herbs, ie, PM extract in improving cognitive function and psychosocial parameter.…”
Section: Discussionmentioning
confidence: 73%
“… 31 In one study, Laditka et al found that most of adults used supplements to treat or cure their cognitive problems rather than to prevent them. 32 Hence, this study provides scientific evidence of beneficial effect of natural herbs, ie, PM extract in improving cognitive function and psychosocial parameter.…”
Section: Discussionmentioning
confidence: 73%
“…Participants were predominantly adults with a small number of studies focussed on older adults 44,57,65,94,95,105,110,113,114 , children 45,58,63,68,73,97,103,106,115,116 , adolescents 41,97 , or all age groups 61,99,112 . More than half of the studies included users of various types of CM (n = 45) 31,35,36,38,4143,50,51,54,5759,61–63,65,66,68,72,73,75,76,80–82,85,88,89,96,97,102113,115,116 , while others were limited to users of specific types of CM such as herbs and/or supplements 3234,37,4447,52,53,55,56,60,64,67,69–71,74,7779,83,86,87,9295,98101,109,114 , yoga 48,91 , tai chi 49,90 , mind-body medicine 40 , practitioner-provided CM 39 , or local traditional medicine 84 .…”
Section: Resultsmentioning
confidence: 99%
“…For increasing numbers seeking to augment their diets for cognitive health, factors such as convenience, cost, and concerns about long-term effects of methyl mercury may motivate the use of fish oil supplements (FOSs) to replace or augment dietary consumption of marine sources of n-3 PUFAs [1]. …”
Section: Introductionmentioning
confidence: 99%